2002
DOI: 10.1590/s0103-84782002000100008
|View full text |Cite
|
Sign up to set email alerts
|

ARMAZENAMENTO DE PÊSSEGOS (Prunus persica L.), CULTIVAR CHIRIPÁ, EM ATMOSFERA CONTROLADA

Abstract: . 6 Engenheiro Agrônomo, PhD. Pesquisador do CPACT-EMBRAPA, Pelotas, RS. RESUMO Uma das principais alterações durante o armazenamento refrigerado de pêssegos é a ocorrência de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
4
0
6
Order By: Relevance
“…This is in accordance with other authors who demonstrated that appearance, flesh color, flesh firmness, juiciness, and flavor are essential attributes for fruit acceptability (SAMS, 1998;MATTHEIS;FELLMAN, 1998;MARTINS et al, 2002;ROMBALDI et al, 2002).…”
supporting
confidence: 93%
“…This is in accordance with other authors who demonstrated that appearance, flesh color, flesh firmness, juiciness, and flavor are essential attributes for fruit acceptability (SAMS, 1998;MATTHEIS;FELLMAN, 1998;MARTINS et al, 2002;ROMBALDI et al, 2002).…”
supporting
confidence: 93%
“…Na maioria dos casos, a colheita dos frutos é realizada em estádios iniciais de maturação com objetivo de prolongar o período de armazenamento. Em conseqüência, a qualidade sensorial dos frutos é baixa quando estas amadurecem e a susceptibilidade a distúrbios fisiológicos e danos mecânicos aumenta (ROMBALDI et al, 2002;FERRER et al, 2005). Por outro lado, a colheita tardia dos frutos resulta em pêssegos com elevada qualidade, porém eles apresentam baixo potencial de armazenamento, sendo mais apropriados ao consumo imediato (ROMBALDI et al, 2002).…”
Section: Introductionunclassified
“…Juiciness and mealiness presented high negative correlation (-0.98), the same way firmness and mealiness (-0.91), certainly the fruits with woollier and drier texture released little amount of juice in chewing and required lower force in the bite. Rombaldi et al (2002) evaluated the storage life of 'Chiripá' peaches under CA (5.0 kPa CO 2 and 1.5 kPa O 2 )…”
Section: Sensory Evaluation Of Samplesmentioning
confidence: 99%